Listen first! : turning social media conversations into business advantage - Rappaport, Stephen D., 1952- (John Wiley & Sons, 2011)
"Listen First! responds to four questions often heard: what is listening to social media, how is it used, how is it done, and where is it headed? Currently there isn't an authoritative source that organizes and synthesizes what is known about social media listening and presents it in a way that was useful for making marketing and branding decisions. This book is the response to fill that void. The author explains the state of the art in social media listening, selecting cases based on solid research that stand up to careful scrutiny and whose methods supported doing excellent listening work. This book will start the conversation on online listening in all companies who want to run more efficiently"--